(untitled) (LEARNing Landscapes, 2016)
In this article, we explore how social work students cultivated a deeper understanding and community connection with older adults through personal engagement with artistic practices. We begin with an exploration of gerontological social work, noting the trends and challenges in this specialization. Guided by extended epistemology as a conceptual framework, we consider the role of the arts within critical pedagogy and describe an undergraduate course taken concurrently during student eld-placements. As part of the curriculum, students designed artifacts about their experience working with older adults, which supported critical re ection and student-led learning. As an exemplar of a creative teaching model, further considerations for implementation are also discussed.